Organizational Slack in Decentralized Firms: The Role of Business Unit Controllers - Indjejikian, Raffi J.; Mat?jka, Michal (The Accounting Review, 2006)
We study the determinants of organizational slack in large decentralized firms and focus in particular on how management accounting systems (represented by business unit controllers) affect slack. We rely on an adverse selection model to derive several predictions and to motivate our tests. Consistent with this framework, we find that organizational slack (measured by achievability of business unit managers' performance targets) is higher in settings where business unit controllers focus relatively more on providing decision-making information to business unit managers than on providing information for corporate control. We also find that organizational slack is persistent over time and positively associated with business unit growth, our proxy for the extent of information asymmetry between corporate headquarters and local business unit management.